Corporate and Dividend Tax Effects in Scholarly Literature: A Bibliometric Analysis - Nilam Rostyana (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - This study employs a bibliometric approach to analyze the evolution of research on corporate and dividend taxation. The analysis elucidates the influence of these topics on corporate behavior, investment decisions, and broader economic outcomes. Method - Data were sourced from 660 Scopus-indexed journal articles published between 1980 and 2025. The bibliographic data were analyzed using the Bibliometrix package in RStudio, employing publication performance, keyword co-occurrence, thematic mapping, and intellectual structure to trace the field’s development over time. Main Findings - The analysis demonstrates a consistent growth in academic interest in corporate and dividend tax research. Thematic clusters reveal that tax avoidance, corporate governance, and dividend policy remain dominant and enduring topics. Emerging themes such as ESG integration, economic policy uncertainty, and digital taxation indicate the field’s expansion toward sustainability and technological adaptation. Theory and Practical Implications - Theoretically, the study enhances the integration of agency theory, stakeholder theory, and institutional economics in explaining how tax systems influence firm behavior and decision-making. Practically, the findings demonstrate that tax policy functions not only as a fiscal instrument but also as a strategic mechanism to enhance transparency, accountability, and corporate resilience in a globalized economy. Novelty - This study presents a comprehensive four-decade mapping of corporate and dividend tax research, elucidating its conceptual transformations and emerging interdisciplinary directions toward sustainability.